2001
DOI: 10.1063/1.1370989
|View full text |Cite
|
Sign up to set email alerts
|

Thickness effects on imprint in chemical-solution-derived (Pb, La)(Zr, Ti)O3 thin films

Abstract: Low-temperature growth of epitaxial LaNiO 3 / Pb(Zr 0.52 Ti 0.48 ) O 3 / LaNiO 3 on Si(001) by pulsed-laser deposition J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
(6 reference statements)
2
10
0
Order By: Relevance
“…The thickness dependence of room temperature (a) longitudinal piezoelectric coefficient and (b) relative permittivity in polycrystalline morphotropic‐composition PZT , polycrystalline PL a ZT 12/50/50 and PL a ZT 12/30/70, polycrystalline PL a ZT 5/30/70, epitaxial morphotropic phase boundary PZT , and epitaxial PbZr 0.2 Ti 0.8 O 3 , 0.30BiScO 3 –0.70PbTiO 3 , and K 0.5 Na 0.5 NbO 3 thin films extracted from several independent experimental studies. Within each dataset the crystallographic texture and preparation procedures are consistent.…”
Section: Domain Grain Size and Thickness Scaling Effectsmentioning
confidence: 96%
“…The thickness dependence of room temperature (a) longitudinal piezoelectric coefficient and (b) relative permittivity in polycrystalline morphotropic‐composition PZT , polycrystalline PL a ZT 12/50/50 and PL a ZT 12/30/70, polycrystalline PL a ZT 5/30/70, epitaxial morphotropic phase boundary PZT , and epitaxial PbZr 0.2 Ti 0.8 O 3 , 0.30BiScO 3 –0.70PbTiO 3 , and K 0.5 Na 0.5 NbO 3 thin films extracted from several independent experimental studies. Within each dataset the crystallographic texture and preparation procedures are consistent.…”
Section: Domain Grain Size and Thickness Scaling Effectsmentioning
confidence: 96%
“…It was found that the latter decreases with decreasing thickness of PZT ferroelectric films. 23,24 This is usually explained by the presence of a thin layer of low dielectric constant at the electrode interfaces ͑the "dead layer"͒, leading to the series capacitor model suggested by Scott et al 25 Later on theories were developed to sustain the presence of the dead layer and thickness dependence of the dielectric constant. [26][27][28][29][30][31][32] Recently it was shown that thickness effects, such as the "smearing" of the ferroelectric transition and the thickness dependence of the dielectric constant and transition temperature, are not intrinsic phenomena in the case of BaTiO 3 ͑BTO͒, SrTiO 3 ͑STO͒, and ͑Ba 0.5 Sr 0.5 ͒TiO 3 ͑BST͒ singlecrystalline thin films.…”
Section: Introductionmentioning
confidence: 99%
“…One experiment result that may indirectly indicate the existence of the charged defects especially defect dipole complexes at the interface was that of the voltage shifts, i.e. the value of V c + – V c − in the polarization loops shown in the following figure, are all about 0.2 V nearly independent of the film thickness; then, we consider that defect dipole complexes may mostly be located at the interface with a similar concentration independence of the film thickness, as the concentration and the distribution of the charged defects in the films will determine the corresponding voltage shift value 30 …”
Section: Resultsmentioning
confidence: 90%
“…the value of V c 1 -V c À in the polarization loops shown in the following figure, are all about 0.2 V nearly independent of the film thickness; then, we consider that defect dipole complexes may mostly be located at the interface with a similar concentration independence of the film thickness, as the concentration and the distribution of the charged defects in the films will determine the corresponding voltage shift value. 30 The dependence of ferroelectric properties on the thickness of the BSPT films at room temperature was presented in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%